Transcription factor 7-like 2 as type-2 diabetes mellitus diagnostic marker in ethnic Minangkabau - Syamsurizal Syamsurizal; Yanwirasti Yanwirasti; Asman Manaf; Jamsari Jamsari; ML Edy Parwanto; Arif Sardi (Faculty of Medicine, Universitas Trisakti, 2014)
BACKGROUNDThe prevalence of type-2 diabetes mellitus (T2DM) has been increasing rapidly in developed and developing countries. Many new loci associated with T2DM have been uncovered by genetic and genome-wide association studies, eg. the transcription factor 7-like 2 (TCF7L2) gene variant rs7895340 has been associated with type-2 diabetes mellitus. The aim of this research was to find an association between polymorphisms of TCF7L2 gene variant rs7895340 with T2DM in ethnic Minangkabau.METHODSThis was a case-control study using a consecutive sampling technique among ethnic Minangkabau patients who came for treatment to the Metabolic Endocrinology Polyclinic at Dr. M. Jamil Hospital. Analysis was performed on 132 subjects (66 T2DM patients and 66 controls). DNA was isolated from venous blood samples and amplified using the amplification refractory mutation system - polymerase chain reaction (ARMS-PCR) method to detect single nucleotide polymorphisms (SNPs) of TCF7L2 gene variant rs7895340. To determine the significance of association of SNPs of rs7895340 with T2DM in ethnic Minangkabau, data analysis was performed using chi-square test.RESULTSThe ARMS - PCR for TCF7L2 gene variant rs7895340 found polymorphisms in 28 (42.42%) subjects with type 2 diabetes mellitus and in 15 (22.72%) non-diabetic subjects.There was a significant association between rs7895340 SNPs with the probability of T2DM in ethnic Minangkabau (OR=2.505, p=0.026). CONCLUSIONSSingle nucleotide polymorphism rs7895340 of TCF7L2 gene can be used as genetic marker of type-2 diabetes mellitus in ethnic Minangkabau.